In vitro investigation into strategies for mucosal delivery of proteins - Vllasaliu, Driton (2010)
Mucosal surfaces offer a potential for non-invasive delivery of proteins. The role of these surfaces, however, is to limit the movement of material from the external environment (mucosal lumen) into systemic circulation. Mucosal absorption of protein therapeutics is constrained through several physiological barriers such as mucus and mucociliary clearance, protease enzymes, epithelial tight junctions (TJs) and cellular membranes. This work explores different strategies with the view to improving the transport of macromolecules (proteins and protein drug models) across polarised epithelial cell layers in vitro, which could potentially be a reflection of improved mucosal absorption and bioavailability in vivo. The Calu-3 cell line was used in this work to produce such layers, serving as an in vitro model of the airway epithelium. Following growth of Calu-3 cells on filters under air-interface culture conditions polarised layers of closely packed cells were formed. The cell layers exhibited a TEER ≥500 Ωcm2 and cells showed structural features similar to the native epithelium, including the TJs, the microvilli and the secretory granules. Cell layers presented a barrier to the permeability of FITC-dextrans (FDs, paracellular markers) and nanoparticles (NPs).